Are dopamine derivatives implicated in the pathogenesis of Parkinson's disease? - Bisaglia, Marco; Filograna, Roberta; Beltramini, Mariano; Bubacco, Luigi (Ageing research reviews, 2014)
•The molecular pathways involved in Parkinson's disease are extensively described.•The aforementioned pathways are linked to the oxidative chemistry of dopamine.•The reactions of dopamine-derived quinones with cellular targets are emphasized.•Dopamine-derived quinones could contribute to the progression of Parkinson's disease. Parkinson's disease (PD) is the most common motor system disorder affecting 1–2% of people over the age of sixty-five. Although PD is generally a sporadic neurological disorder, the discovery of monogenic, hereditable forms of the disease, representing 5–10% of all cases, has been very important in helping to partially delineate the molecular pathways that lead to this pathology. These mechanisms include impairment of the intracellular protein-degradation pathways, protein aggregation, mitochondria dysfunction, oxidative stress and neuroinflammation. Some of these features are also supported by post-mortem analyses. One of the main pathological hallmarks of PD is the preferential degeneration of dopaminergic neurons, which supports a direct role of dopamine itself in promoting the disorder. This review presents a comprehensive overview of the existing literature that links the aforementioned pathways to the oxidative chemistry of dopamine, ultimately leading to the formation of free radicals and reactive quinone species. We emphasize, in particular, how the reaction of dopamine-derived quinones with several cellular targets could foster the processes involved in the pathogenesis of PD and contribute to the progression of the disorder.